2015
DOI: 10.1590/0001-3765201520150364
|View full text |Cite
|
Sign up to set email alerts
|

Eggshell and Histology Provide Insight on the Life History of a Pterosaur with Two Functional Ovaries

Abstract: The counterpart of a previously described non-pterodactyloid pterosaur with an egg revealed the presence of a second egg inside the body cavity of this gravid female. It clearly shows that pterosaurs had two functional oviducts and demonstrates that the reduction of one oviduct was not a prerequisite for developing powered flight, at least in this group. Compositional analysis of one egg suggests the lack of a hard external layer of calcium carbonate. Histological sections of one femur lack medullary bone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
0
27
0
2
Order By: Relevance
“…To date, embryos and/or eggs have been reported in four species of pterosaur representing three distinct Late Jurassic -Early Cretaceous clades ( [1][2][3][4][5][6][7][8]; electronic supplementary material, table S1). These finds have provided critical insights into the reproductive biology of pterosaurs which, as in basal amniotes, seems to have involved paired ovaries, relatively small, ovoidal, pliable-shelled eggs and incubation via burial in substrate rather than bodily contact [4,5,7]. It has generally been assumed that hatchlings were altricial and required extended parental care before achieving flight, as in extant species of bats and many birds [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…To date, embryos and/or eggs have been reported in four species of pterosaur representing three distinct Late Jurassic -Early Cretaceous clades ( [1][2][3][4][5][6][7][8]; electronic supplementary material, table S1). These finds have provided critical insights into the reproductive biology of pterosaurs which, as in basal amniotes, seems to have involved paired ovaries, relatively small, ovoidal, pliable-shelled eggs and incubation via burial in substrate rather than bodily contact [4,5,7]. It has generally been assumed that hatchlings were altricial and required extended parental care before achieving flight, as in extant species of bats and many birds [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Aerodynamic models of bone strength analyses and wing-loading forces have revealed that pterosaurs potentially flew with high manoeuvrability (Palmer, 2011;Habib & Hall, 2012;Habib & Witton, 2013), and likely utilised energy-efficient quadrupedal take-offs (Habib, 2008). Pterosaur phylogeny (Kellner, 2003;Unwin, 2003;Lü et al, 2010;Andres, Clark & Xu 2014), ground-based behaviours elucidated from trace fossils (ichnofossils) (Hwang et al, 2002;Xing et al, 2012;Fiorillo et al, 2015) and reproductive biology (Chiappe et al, 2004;Grellet-Tinner et al, 2007;Lü et al, 2011a;Wang et al, 2015Wang et al, , 2017 have also seen major advances. One area of pterosaur research lagging behind, however, is understanding of their dietary ecology (Unwin & Henderson, 2002;Hone, 2012;Hone et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…2d) and was associated with not only one, but two eggs, one still inside the body of the animal (Wang et al 2015) and therefore can be confidently regarded as a female. However, there are other aspects of the study of Lü et al (2011a) which are more problematic.…”
Section: Discussionmentioning
confidence: 99%